Optimal placement of actuator for vibration suppression based on intelligent PID controller - Muhamad Sukri, Hadi; Nadzirah, Mohd Mokhtar; Intan Zaurah, Mat Darus (Institute of Electrical and Electronics Engineers Inc., 2020)
Many attempts have been proposed by the previous researchers due to reduce the undesired vibration by considering several control strategies. The simplest way in reducing the vibration is to build more rigid structure so that less vibration will be produced. Nevertheless, this strategy is usually not applicable since the structures are need high power consumption and limitation in operation speed. Furthermore, it becomes a growing trend among the industries to use light weight of mechanical structure known as flexible plate. However, the critical problem faced by the industries is vibration on the structure that can lead to structural damage. Hence, this research presents the optimal placement of actuator and sensor on the experimental rig for vibration cancelation of the flexible plate structure based on intelligent PID controller. The PID controller tuned by artificial bee colony (ABC) algorithm was used to control the undesired vibration on the structure. The robustness of developed controller was validated by varying the position of actuator on the experimental rig. It was indicated that point A2 leads to the good attenuation level by achieving highest attenuation value at the first mode of vibration with 28.83 dB which is equivalent to 21.62 % attenuation, after the introduction of vibration control.